2023
DOI: 10.1021/acsomega.2c05107
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Synthesis, Characterization, and Photocatalytic Activity of TiO2 and Cr-Doped TiO2 for the Degradation of p-Chlorophenol

Abstract: TiO2 and Cr–TiO2 nanoparticles (NPs) have been synthesized by the sol–gel method using titanium isopropoxide as the precursor of Titania. The prepared samples were analyzed by employing scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Fourier transform infrared analyses. Under UV irradiation, the photocatalytic activities of TiO2 and Cr–TiO2 were observed by estimating the % degradation of p-chlorophenol (PCP) as a sample pollutant. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…reported that DN-FSP facilitates the engineering of various catalytic heterojunctions, such as FeO x /Al 2 O 3 and MnO x /Al 2 O 3 , which exhibited superior catalytic performance in CO conversion compared to materials produced using SN-FSP. In a broader sense, the impact of the synthesis method on photocatalytic activity has been well-established in the literature. This study demonstrates that DN-FSP technology is highly effective for the one-step production of ultrafine Rutile-RuO 2 dispersed on a rutile-TiO 2 surface, proving to be very efficient in photocatalytic H 2 and O 2 production under solar light irradiation.…”
Section: Discussionmentioning
confidence: 76%
“…reported that DN-FSP facilitates the engineering of various catalytic heterojunctions, such as FeO x /Al 2 O 3 and MnO x /Al 2 O 3 , which exhibited superior catalytic performance in CO conversion compared to materials produced using SN-FSP. In a broader sense, the impact of the synthesis method on photocatalytic activity has been well-established in the literature. This study demonstrates that DN-FSP technology is highly effective for the one-step production of ultrafine Rutile-RuO 2 dispersed on a rutile-TiO 2 surface, proving to be very efficient in photocatalytic H 2 and O 2 production under solar light irradiation.…”
Section: Discussionmentioning
confidence: 76%
“…The photocatalytic activity of Fe-doped TiO 2 and ZnO has been reported to be greater than that of their undoped counterparts [21,22]. Transition metals, such as copper (Cu), chromium (Cr), and vanadium (V), have been studied for their potential to enhance the photocatalytic performance of metal oxides [23][24][25]. A photocatalytic system that harnesses visible light is crucial to producing clean energy and restoring the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Among many types of photocatalysts, anatase TiO 2 is the most widely applicable owing to its excellent photocatalytic activity, non-toxicity and low cost. 1,2 However, TiO 2 can only absorb 5% UV radiation from sunlight due to its wide band gap of 3.2 eV. 3 Moreover, the photogenerated e À and h + in TiO 2 are likely to recombine, leading to a low utilization of photogenerated carriers.…”
Section: Introductionmentioning
confidence: 99%